2021
DOI: 10.2196/24120
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Clinical Decision Support Based on Recurrent Neural Networks for In-Hospital Acute Kidney Injury: External Validation and Model Interpretation

Abstract: Background Acute kidney injury (AKI) is commonly encountered in clinical practice and is associated with poor patient outcomes and increased health care costs. Despite it posing significant challenges for clinicians, effective measures for AKI prediction and prevention are lacking. Previously published AKI prediction models mostly have a simple design without external validation. Furthermore, little is known about the process of linking model output and clinical decisions due to the black-box natur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 54 publications
1
15
0
Order By: Relevance
“…Due to the complexity of SA-AKI, the clinical model integrating routine parameters may be more effective for predicting short-term reversibility of AKI than any parameter considered alone. A possible way to achieve this is to utilize advanced machine learning approaches, which have been applied in the prevention and management of AKI, such as predicting the development of AKI 37 41 , volume responsiveness in patients with oliguria 42 and mortality in critically ill AKI patients 43 45 . Our study corroborated the promise indicated by these previous studies and extended them by demonstrating the applicability of machine learning methods for predicting persistent AKI in a large cohort of SA-AKI patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the complexity of SA-AKI, the clinical model integrating routine parameters may be more effective for predicting short-term reversibility of AKI than any parameter considered alone. A possible way to achieve this is to utilize advanced machine learning approaches, which have been applied in the prevention and management of AKI, such as predicting the development of AKI 37 41 , volume responsiveness in patients with oliguria 42 and mortality in critically ill AKI patients 43 45 . Our study corroborated the promise indicated by these previous studies and extended them by demonstrating the applicability of machine learning methods for predicting persistent AKI in a large cohort of SA-AKI patients.…”
Section: Discussionmentioning
confidence: 99%
“…Le et al proposed a convolutional neural networks prediction system, which outperformed the XGB model and the SOFA score in predicting AKI 48 h before onset in ICU patients 40 . Similarly, Kim et al used recurrent neural network to assess future AKI occurrence and individualized AKI risk factors in real time among hospitalized patients 41 . Hofer et al applied the deep neural networks to create models for postoperative AKI, mortality, reintubation, and the combined outcome, which exhibited superior performance to the ASA score 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Two RNN algorithms were created using a dataset of more than 72,000 patients. [72] Model 1 predicted the occurrence of AKI within 7 days with AUROC of 0.84 and model 2 predicted the future trajectory of creatinine values up to 72 hours with AUROC of 0.9. Further development of the suggested approaches could incorporate the model into CDS systems for prediction of in-hospital AKI.…”
Section: Resultsmentioning
confidence: 99%
“…RNN models capture the temporal nature of EHR, imaging and other medical data to predict diseases, complications, and outcomes. [66][67][68][69][70][71][72][73] Deep learning models produce higher accuracy but suffer from issues of interpretability and instability. [15,75] Combinations of traditional and deep learning models could address challenges of interpretability and accuracy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation